Peran Pemerintah Kota Depok Dalam Mengatasi atau Mengurangi Kemacetan Lalu Lintas Di Kota Depok - Ilham Reza Perdana (to-ra, 2021)
The study considers the role of the depok government in addressing or reducing traffic jams in the city of depok, to aim to identify the causes caused by traffic jams in depok city, and then after knowing there was a definite cause or effect because of the cause of the traffic jam. Knowing all of this should be the same question as to what measures governments are taking to address the problem of reducing or addressing the traffic jam. The approach taken in this study was normative jurisdiction, which is that by examining library or secondary data materials asa basis for study by examining the associated regulations and literature deals with traffic congestion. The study is a descriptive analysis that describes in detail and systematically the problems that occurred and are analyzed according to hokum theory asa sequence of data and rules.